In depth study of Malaysian standard form of construction contracts - Oh, Chin Phang (Universiti Malaysia Sarawak, UNIMAS, 2010)
The PWD forms of contract are the de facto standard forms of contraction contract used by the Malaysian public sector and most of these big scaled projects are publicfunded which makes government a major player in the construction industry. PWD standard form has gone through revision from PWD 203A Forms (Rev. 83) to PWD 203A Forms (Rev. 2007) to make it a better tool in governing project condition. This research is aimed to carry out an in-depth study of all the clauses stated in PWD 203A (Rev. 2007) standard form of construction contract from a view of neutral party and determine the adequacy of application of every clauses in the Malaysia construction industry. Questionnaires used to collect the public’s opinion on the degree of importance on the eight (8) elements identified as essential to a contract form in Malaysia construction Industry, namely: clarity, comprehensiveness, completeness, consistency, flexibility, clear structured project management framework, fairness or role distribution and risk distribution. There are seventy eight (78) clauses have been analyzed and evaluate the overall performance of clauses based on the total evaluation score with seven magnitude of evaluation such as low negative, average negative, high negative, neutral, low positive, average positive and high positive. Through this research, the effectiveness and application of the revised version of PWD 203A (Rev. 2007) in Malaysian construction industry is considered as average positive evaluation and several recommendations have been suggested in order to improve the overall performances of clauses.